Optimization of a Modular Nanotransporter Design for Targeted Intracellular Delivery of Photosensitizer - Rena T. Alieva; Alexey V. Ulasov; Yuri V. Khramtsov; Tatiana A. Slastnikova; Tatiana N. Lupanova; Maria A. Gribova; Georgii P. Georgiev; Andrey A. Rosenkranz (MDPI AG, 2024)
Modular nanotransporters (MNTs) are drug delivery systems for targeted cancer treatment. As MNTs are composed of several modules, they offer the advantage of high specificity and biocompatibility in delivering drugs to the target compartment of cancer cells. The large carrier module brings together functioning MNT modules and serves as a platform for drug attachment. The development of smaller-sized MNTs via truncation of the carrier module appears advantageous in facilitating tissue penetration. In this study, two new MNTs with a truncated carrier module containing either an N-terminal (MNTN) or a C-terminal (MNTC) part were developed by genetic engineering. Both new MNTs demonstrated a high affinity for target receptors, as revealed by fluorescent-labeled ligand-competitive binding. The liposome leakage assay proved the endosomolytic activity of MNTs. Binding to the importin heterodimer of each truncated MNT was revealed by a thermophoresis assay, while only MNTN possessed binding to Keap1. Finally, the photodynamic efficacy of the photosensitizer attached to MNTN was significantly higher than when attached to either MNTC or the original MNTs. Thus, this work reveals that MNT's carrier module can be truncated without losing MNT functionality, favoring the N-terminal part of the carrier module due to its ability to bind Keap1.